Conceptions of the educational research practice of detailing in the training of teachers in basic education : Conceptions of the educational research practice of detailing in the training of teachers in basic education - Pablo Andrés García Sandoval, Andrés Julián Guzmán Sierra (Revista de Orientación Educacional, 2019)
Se caracterizó las concepciones de Práctica Pedagógica Investigativa y Profundización de los maestros en formación de la Licenciatura en Educación Básica de X semestre pertenecientes a los CREAD más grandes y representativos de la Facultad de Estudios a Distancia de la Universidad Pedagógica y Tecnológica de Colombia. Mediante la investigación descriptiva y el enfoque cualitativo se contempló el abordaje de cuatro categorías de análisis las cuales permiten reconocer los discursos y actuaciones de los maestros practicantes. Para la recolección de información se ejecutó una encuesta estructurada con 10 preguntas que se relacionan con las categorías de análisis. Se presentan gráficas discriminando las respuestas por frecuencia e interés mostrando como resultado diferentes posturas intelectuales y juicios con relación al proceso formativo del maestro. Como conclusión, los maestros en formación conciben la práctica pedagógica como el espacio ideal para poner aplicar los conocimientos aprendidos durante el transcurso del ciclo de preparación profesional en el programa académico de la licenciatura. En este sentido, una vez confrontados los resultados y posturas teóricas se evidencia que dichas concepciones se manifiestan bajo parámetros hermenéutico-reflexivos. Palabras Clave: Práctica pedagógica, Concepciones, Maestros en Formación. Abstract: The conceptions of educational research practice of detailing in the training of teachers in the bachelor’s degree in basic education were typified; the sample of this study was the students of the Pedagogical and Technological University of Colombia, who are attending the tenth semester in the most representative CREAD of the faculty of distance studies. The use of the descriptive research and a qualitative approach allowed considering four categories of analysis that recognize the speeches and performances from the training teachers. It was executed a structured survey with 10 questions that correspond to the mentioned categories previously. This paper presents some series of graphics, selecting the answer by frequency and interests, the results evince different intellectual stances and opinions related to the learning process of the student in the educational research practice of detailing. In conclusion, teachers in training come up with the pedagogical practice as the ideal space to apply the knowledge learned during the cycle of professional preparation in the academic program of the bachelor's degree. In this sense, once confronted the results and theoretical positions it is clear that these conceptions are manifested under the parameters hermeneutical-reflective. Keywords: educational training, conceptions, training teachers.